PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCHUNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDNEGERI157KOTA PEKANBARU - Dinda Pratiwi; Hendri Marhadi; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstrakThis study aims to improve learning outcomes IPS 157 fourth grade students of SDN Pekanbaru City School Year 2012/2013 through the "Implementation cooperative learning model make a match".This research was conducted in November until November 2012 . Subjects were 157 fourth grade students of SDN Pekanbaru 41 people as the number of students, which consisted of 21 male students and 20 female students. This research is a form of action research class consisting of 2 cycles. Cycle I consists of 2 meetings and on to the second cycle consists of 2 meetings. Research data shows that the learning outcomes of students has increased, which prior to the act of cooperative learning model Make A Match of as many as 41 students only 4 students ( 9.8 % ) were scored daily tests over a minimum completeness criteria ( KKM ) is has been determined by the school is 67. While as many as 37 students ( 90.2 % ) is still below the KKM . After the act of cooperative learning model Make A Match in the first cycle average daily test cycle II are 79 and 86 with the increase of cycle I to cycle II of 8. While the average percentage of students in the classical mastery learning derived from daily tests have increased in the first cycle is 49 (category yet complete) and a 49 second cycle (categories completed). Average activity of teachers in fostering the learning process with the action on the first cycle is 67.86 % (both categories) while the second cycle is 96.43 % (category very well) and learning activities of students during the learning process takes place in the first cycle, namely 60,71 % and the second cycle on average 92.86 % .Keywords:Make a Match, The Result Of Social Studies